017 Case study of a computer decision support system for emergency care: the impact on the ambulance control room. Issue 3 (1st March 2011) - Turnbull, Joanne; Calestani, Melania; Pope, Catherine; Halford, Susan; Prichard, Jane
Abstract : Background: Clinical decision support systems (CDSS) designed to assist healthcare staff with decision-making, are diffusing rapidly across the NHS for triage in urgent and emergency care. A new CDSS (NHS Pathways) is designed for use by non-clinical call handlers in these settings. CDSS have potential to improve decision-making (faster, more accurate, efficient, safer, more evidence-based), whilst offering opportunities to change workflow and workforce configuration. However, the implementation of such technologies depends on the interplay between the technology and the workforce in everyday practice. Aims: Here we examine how a CDSS is used by 999 call handlers, focussing upon the impact of new technology on everyday work, and the skills needed, in an ambulance control room. Methods: We are undertaking a comparative mixed-method case study using ethnographic and survey methods to describe the design, development, management and use of the CDSS. The Normalisation Process Model provides a theoretical framework for the study. Results: We have observed a general intensification of labour and an emphasis on a multi-tasking approach (increased activity, components and tasks, greater mental effort). The CDSS has, paradoxically, brought about a (re)clinicalisation of the work. The claim for the CDSS is that the work does not require clinical expertise but we suggest that the interaction between call handlers and the system allows staff to embody clinical knowledge, creating new types of expertise and skills. Conclusions: Although only halfway through our study, this poster highlights some of the complexities in introducing new technologies into emergency settings. The CDSS has impacted on the nature of the work, and the arrangement and division of labour within the service. Technologies like this CDSS do not work in isolation—they require work by organisations and individuals to come into use.